Management of genetic diseases: Present and future: Tratamiento de las enfermedades genéticas: Presente y futuro - Abarca Barriga, Hugo Hernán (2021)
Today, the number of genetic diseases is around 10000 conditions, affecting to 6%-8% of all populations. This review shows us how the discovery of genetic variants in our genome, this facilitated to know with precision about the mechanisms physiopathological, and hence to recognize those target points susceptible to modifications, through therapeutical strategies different with palliative proposals, increase life expectancy, or improve qualities of life. These therapies are diverse, using drugs for polygenic diseases, nutritional therapy, special formulas, enzyme replacement therapies, hematopoietic stem cell transplant, substrate reduction, oligonucleotides, and gene therapy. These genetic diseases are heterogeneous clinically with a very low frequency; nevertheless, open to the possibility of research in new strategies for more genetic disease, that today, furthermore, are orphans.